Commercial Pressures and Editorial Independence: Egyptian Journalists' Perceptions of Advertiser Influence in Contemporary Media - Salem, Mohamed Ahmed (AUC Knowledge Fountain, 2025)
This thesis explores the complex interplay between commercial imperatives and editorial autonomy in Egypt’s contemporary media landscape, focusing on journalists’ perceptions of advertising influence. Drawing on Cognitive Dissonance Theory (CDT) and informed by Political Economy and Institutional Theory, the study investigates how Egyptian journalists navigate ethical tensions arising from advertiser demands—both state-linked and private—within a hybrid media system marked by economic precarity, political control, and digital disruption. Through 20 in-depth interviews with journalists, alongside insights from PR professionals, media managers, and academic experts, the research reveals a pervasive erosion of the editorial-commercial boundary. Journalists report widespread self-censorship, blurred content labelling, and managerial pressure to prioritize advertiser interests, often rationalized through coping strategies such as compliance, compartmentalization, and avoidance. Digital advertising intensifies these pressures via metrics-driven content production and native advertising formats. Despite formal regulatory frameworks mandating editorial independence, enforcement remains weak, and internal codes of ethics are often inaccessible or symbolic. The findings underscore a systemic entanglement of journalism with commercial and political forces, highlighting the psychological burden on practitioners and the normalization of ethical compromise. This study contributes to global media ethics discourse by contextualizing CDT within a non-Western authoritarian-commercial media system and offers practical implications for policy reform, newsroom leadership, and journalism education.